Visualizing a Field of Research With Scientometrics: Climate Change Associated With Major Aquatic Species Production in the World - Azra, Mohamad N.; Mohd Noor, Mohd Iqbal; Sung, Yeong Yik; Abd Ghaffar, Mazlan (Frontiers in Environmental Science, 2022)
Climate change research on major aquatic species assists various stakeholders (e.g. policymakers, farmers, funders) in better managing its aquaculture activities and productivity for future food sustainability. However, there has been little research on the impact of climate change on aquatic production, particularly in terms of scientometric analyses. Thus, using the bibliometric and scientometric analysis methods, this study was carried out to determine what research exists on the impact of climate change on aquatic production groups. We focused on finfish, crustaceans, and molluscs. Data retrieved from Web of Science and Scopus was mapped with CiteSpace and used to assess the trends and current status of research topics on climate change associated with worldwide aquatic production. We identified ocean acidification as an important research topic for managing the future production of aquatic species. We also provided a comprehensive perspective and delineated the need for: (i) more international collaboration for research activity focusing on climate change and aquatic production in order to achieve the United Nations Sustainable Development Goal by 2030; (ii) the incorporation of work from molecular biology, economics, and sustainability.